Efektivitas Media Audio Visual dan Ular Tangga Cuci Tangan Terhadap Pengetahuan Anak Usia Sekolah - Nutrisia Nu'im Haiya; Iwan Ardian (LPPM Hang Tuah Pekanbaru, 2023)
Introduction: Education through health education is one of the efforts to prevent diarrhea in children. The key to the success of health education for children lies in the media used, snakes and ladders media and audio-visual media are media that can be used in health education for children, but there has been no research related to differences in their effectiveness on knowledge about hand washing in school-age children. Methods: Experimental research with a quasi-experimental design with nonequivalent pretest-posttest technique, random sampling being a sampling technique, with school-age children as respondents and a total of 80 respondents consisting of 40 health education intervention groups with snakes and ladders media and 40 audio-visual media intervention groups. data were measured before and after the intervention in both groups, and data were analyzed by the Wilcoxon test and Mann-Whitney test. Results: The snake and ladder media was effective in increasing children's knowledge with p value 0.001 <0.05 and audio-visual media was equally effective in increasing children's knowledge with p value 0.008 <0.05, while the Mann-Whitney test showed that there was no significant difference in posttest results between the intervention groups with a value of 0.241> 0.05. Conclusion: Snakes and ladders media and audio-visual media are equally effective in increasing children's knowledge about hand washing, so this can become a media basis for health promotion by related stakeholders.